2010
DOI: 10.1029/2009gc002836
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the 410 km discontinuity low‐velocity layer beneath the LA RISTRA array in the North American Southwest

Abstract: [1] Receiver functions recorded by the 54-station 920 km long Program for Array Seismic Studies of the Continental Lithosphere-Incorporated Research Institutions for Seismology Colorado Plateau/Rio Grande Rift Seismic Transect Experiment (LA RISTRA) line array display a pervasive negative polarity P to S conversion (P d s) arrival preceding the positive polarity 410 km discontinuity arrival. These arrivals are modeled as a low-velocity layer atop the 410 km discontinuity (410-LVL) and are inverted for a veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 72 publications
2
31
2
Order By: Relevance
“…Schmandt et al (2011) found in P receiver functions a low-velocity zone at 25-60 km above the 410 in several regions in the western United States. Jasbinsek et al (2010) found a low-velocity zone above the 410 at the Colorado Plateau and Rio Grande Rift. Chu et al (2012) found also a low-velocity zone atop the 410 in the United States using wideangle earthquake records.…”
Section: Sharpness Of 410 and 660mentioning
confidence: 95%
“…Schmandt et al (2011) found in P receiver functions a low-velocity zone at 25-60 km above the 410 in several regions in the western United States. Jasbinsek et al (2010) found a low-velocity zone above the 410 at the Colorado Plateau and Rio Grande Rift. Chu et al (2012) found also a low-velocity zone atop the 410 in the United States using wideangle earthquake records.…”
Section: Sharpness Of 410 and 660mentioning
confidence: 95%
“…We note however that this is less than reported in the studies of Jasbinsek and Dueker [] and Jasbinsek et al . [].…”
Section: Mapping the Discontinuitiesmentioning
confidence: 99%
“…The LVL‐410 was initially discovered beneath northeast Asia by Revenaugh and Sipkin [] using seismic waves reflected at the core‐mantle boundary (multiple‐ ScS reverberation). Later seismic studies using a similar technique [ Courtier and Revenaugh , ; Bagley et al , ], receiver functions [ Vinnik and Farra , ; Vinnik et al , ; Fee and Dueker , ; Jasbinsek and Dueker , ; Vinnik and Farra , ; Wittlinger and Farra , ; Leahy , ; Jasbinsek et al , ; Schaeffer and Bostock , ; Tauzin et al , ; Vinnik et al , ; Schmandt et al , ; Huckfeldt et al , ; Bonatto et al , ; Morais et al , ; Thompson et al , ; Liu et al , ], and body wave triplications [ Song et al , ; Gao et al , ; Obayashi et al , ] suggest the widespread existence of this LVL (Figure and supporting information Table S1). In addition, an electromagnetic study in the southwestern U.S. also suggests a layer with high conductivity near the 410 km discontinuity [ Toffelmier and Tyburczy , ].…”
Section: Introductionmentioning
confidence: 98%
“…Previous observations of an LVL‐410 under continents and continental margins [ Revenaugh and Sipkin , ; Vinnik and Farra , ; Vinnik et al , ; Fee and Dueker , ; Song et al , ; Gao et al , ; Obayashi et al , ; Courtier and Revenaugh , ; Jasbinsek and Dueker , ; Toffelmier and Tyburczy , ; Vinnik and Farra , ; Wittlinger and Farra , ; Bagley et al , ; Leahy , ; Jasbinsek et al , ; Schaeffer and Bostock , ; Tauzin et al , ; Vinnik et al , ; Schmandt et al , ; Huckfeldt et al , ; Tauzin et al , ; Bonatto et al , ; Morais et al , ; Thompson et al , ; Liu et al , ]. Digits indicate the reference numbers listed in supporting information Table S1.…”
Section: Introductionmentioning
confidence: 99%